Does cranberry extract reduce antibiotic use for symptoms of acute uncomplicated urinary tract infections (CUTI)? A feasibility randomised trial - Gbinigie, O; Allen, J; Williams, N; Moore, M; Hay, AD; Heneghan, C; Boylan, A-M; Butler, CC (BMJ Publishing Group, 2021)
Objectives To determine the feasibility of conducting a randomised trial of the effectiveness of cranberry extract in reducing antibiotic use by women with symptoms of acute, uncomplicated urinary tract infection (UTI). Design Open-label feasibility randomised parallel group trial. Setting Four general practices in Oxfordshire. Participants Women aged 18 years and above presenting to general practice with symptoms of acute, uncomplicated UTI. Interventions Women were randomly assigned using Research Electronic Data Capture in a 1:1:1 ratio to: (1) immediate antibiotics alone (n=15); (2) immediate antibiotics and immediate cranberry capsules for up to 7 days (n=15); or (3) immediate cranberry capsules and delayed antibiotics for self-initiation in case of non-improvement or worsening of symptoms (n=16). Primary and secondary outcome measures The primary outcome measures were: rate of recruitment of participants; numbers lost to follow-up; proportion of electronic diaries completed by participants; and acceptability of the intervention and study procedures to participants and recruiters. Secondary outcomes included an exploration of differences in symptom burden and antibiotic use between groups. Results Four general practitioner practices (100%) were opened and recruited participants between 1 July and 2 December 2019, with nine study participants recruited per month on average. 68.7% (46/67) of eligible participants were randomised (target 45) with a mean age of 48.4 years (SD 19.9, range 18–81). 89.1% (41/46) of diaries contained some participant entered data and 69.6% (32/46) were fully complete. Three participants (6.5%) were lost to follow-up and two (4.4%) withdrew. Of women randomly assigned to take antibiotics alone (controls), one-third of respondents reported consuming cranberry products (33.3%, 4/12). There were no serious adverse events. Conclusions It appears feasible to conduct a randomised trial of the use of cranberry extract in the treatment of acute, uncomplicated UTI in general practice. Trial registration number ISRCTN Registry (ID: 10399299).